Security of tenure and land registration in Africa : literature review and synthesis - Dickerman, Carol Wilson; Barnes, Grenville (Land Tenure Center, University of Wisconsin-Madison, 1989)
In 1984, the Land Tenure Center embarked on a project to evaluate the experiences with land registration and tenure reform in Africa . The goal was to determine is African states been able to use tenure reform and land registration to provide greater security of tenure than was available through customary tenure systems. Donor agencies focused attention on the creation of individual freehold title, emphasizing the heightened security of holding, marketability, and access to credit under such tenure. National governments, on the other hand, were more concerned to see that land was used productively rather than merely accumulated for purposes of prestige or inheritance or as a hedge against inflation, and for this reason have tended to favor granting more circumscribed rights, such as leaseholds or rights of occupancy. This literature review and synthesis was prepared as part of an effort to increase very substantially our knowledge, especially on a quantitative level, of tenure and development relationships in Africa . The literature review is an attempt to gather in one place data about the diverse efforts at land registration and to describe briefly for each country the various registration programs that have taken place (if any), why they were undertaken, and what subsequent studies of these programs have found. Among other things, it will be seen that the intended benefits, and beneficiaries, of land registration have changed over the century or so since the first systems were put in place. In addition to these variations over time, there are also differences among Anglophone, Francophone, and Lusophone countries, differences that not only influenced the structure of registration systems established during the colonial era, but also continue to inform the kinds of registration systems adopted today.
xxxi, 316 p.
Keywords: Land titles Africa; Land titles Bibliography Africa; Tenure security (Natural resources) Africa; Land tenure Law and legislation Africa; Land administration Africa; Land administration Bibliography Africa